The Birth of a Detective Story from the Spirit of Fantasy - Tomáš Horváth (Slovenska Literatura, 2006)
The aim of the study is to make a research in genealogic and structural relationship between a genre of fantasy and a detective story. The relationship of both two genres was demonstrated through series of interpretations of particular texts not following strictly a historical line, but rather logic of structural transformations. Following it a typological classification was made. Types of the texts mutually differentially defined through logical relationships: inclusive relationship between fantasy (also horror) and detective story (detective segment of investigation incorporated into a text of fantasy or horror, while function of this segment in the detective story and fantasy/horror is reversed), reversed inclusion of fantasy to a genre of a detective story (from the first appearance supernatural thing is logically explained by empiric way), exclusion between a detective story and horror (a detective genre does not have to contain really supernatural motives) and relationship of unique synthesis between a detective story and a fantasy (when a detective story is completely incorporated within fantasy, or a narrative structure contains two parallel stories – detective one and a fantasy). Excluding supernatural forces from the detective story operate in economy of a superior regime of rules of fair play of a detective story (equalities of chances for a reader as well as a detective, providing by pure rationalistic solution). If there is a distributed supernatural explanation in the text, which in its exposition (and etiquette on the cover) activates detective story reader´s generic expectations, pre-programmed detective story reader classifies it as a cheat, as a breaking of a genre pact of a reader with the text. Different genres construct their specific fictional worlds with not breakable rules – breaking of them produces an overlap into a text of a different genre.